Development on Mechatronics : A Multidisciplinary Approach - Johari Halim Shah Osman author; Yusei Tsuboi author; Osamu Ono author; Mohamad Shukri Abdul Manaf author; Rubiyah Yusof author; Mohd. Shafawi author; Hazlina Selamat author; Shamsuddin Mohd. Amin author; Salinda Buyamin author; Herlina Abdul Rahim, 1973-, author; Mohamed Sultan Mohamed Ali editor; Tri, Basuki Kurniawan, 1974-, author; et al. (Skudai : Penerbit Universiti Teknologi Malaysia, 2008)
Includes bibliographical references and index